Exploring user perceived beliefs, evaluations, and gratifications in ASM: applying expectancy-value approach for U&G theory on Mastodon instance Liker.social - Liao, Kai Hung (Frontiers in Communication, 2023)
This study aims to explore users' perceived beliefs of the decentralized alternative social media (ASM), selecting one of Mastodon instances, Liker. social, as the unique case of exploratory investigation. The study employs the online exploratory survey method and uses purposive sampling to identify 152 valid users actively engaged in the Liker.social. Based on the expectancy-value approach to uses and gratifications theory, the study identifies two factors within users' subjective perceived beliefs: informative decentralized benefits and descriptive centralized benefits. The study also finds that the “Writing messages” is the most important functionality evaluated by users but gets fewer level of gratifications obtained, representing that there is still room for improvement. Additionally, the study presents four types of users based on their combined perceived beliefs: (1) All-benefit Rejectors, (2) All-benefit Obtainers, (3) Former-benefit Conservatives, and (4) Newer-benefit Seekers. Users (2) and (4) stressed more value on overall functionality and obtained more gratifications than users (1) and (3), so users (2) and (4) are the same statistically, having greater evaluations of importance and gratifications obtained for Liker.social than that of users (1) and (3). It signifies that the different users held varying beliefs about the benefits brought by the decentralized ASM. It was concluded that the casual relationship is valid: users' evaluations of importance, informative decentralized benefits combined with descriptive centralized benefits eventually affect the level of users' gratifications obtained on the decentralized ASM. Therefore, further research is needed to pay greater attention to users' feedback and experiences on the decentralized ASM.